2022
DOI: 10.3389/fpubh.2022.981233
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical characteristics between patients with seasonal influenza and patients infected by the wild type or delta variant of SARS-CoV-2

Abstract: BackgroundWe compared the clinical characteristics of the patients with COVID-19, infected by the wild type or delta variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), in connection with those of patients with seasonal influenza, all in mild cases.MethodsWe retrospectively studied 245 and 115 patients with mild COVID-19 infected by the wild type and the delta variant of SARS-CoV-2, respectively, with their demographic information, medical history, and laboratory data from hospital records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
5
1
Order By: Relevance
“…Regarding SARS-CoV-2-specific indicators, our results and previous results showed that there was no significant difference in Ct values between Delta and Omicron variants ( Hu et al, 2022 ). Our results and previous results showed that the absolute WBC count was significantly lower in the Delta group than the WT group ( Hu et al, 2022 ; Zhang et al, 2022 ). Moreover, the absolute T lymphocyte, WBC, RBC, eosinophil, and basophil counts were significantly lower in the Delta group than the WT and/or Omicron groups.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Regarding SARS-CoV-2-specific indicators, our results and previous results showed that there was no significant difference in Ct values between Delta and Omicron variants ( Hu et al, 2022 ). Our results and previous results showed that the absolute WBC count was significantly lower in the Delta group than the WT group ( Hu et al, 2022 ; Zhang et al, 2022 ). Moreover, the absolute T lymphocyte, WBC, RBC, eosinophil, and basophil counts were significantly lower in the Delta group than the WT and/or Omicron groups.…”
Section: Discussionsupporting
confidence: 72%
“…This may be due to clinical differences between imported and indigenous cases. Besides, the number of Omicron cases ( n = 20) in the study by Zhang et al (2022c) was relatively small.…”
Section: Discussionmentioning
confidence: 91%
“…At this point , hypertension is the most common complication of COVID-19 patients which subsequently lead to a distrupt in potassium balance and increase in sera K levels (14). Similarly, it has been reported that K levels was significantly higher in the severe COVID-19 patients compared with the non severe cases and the outcomes revealed a positive relationship between the COVID-19 infection and higher levels of potassium in the blood stream (15). The prevalence of hyperkalemia in COVID-19 patients may be reflected firstly by pre-existing clinical conditions that are regarded as risk factors for the development of severe COVID-19 cases , (14) and secondly by the acute kidney injury as a complication of COVID-19 infection because it has been reported that serum urea was increased in severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 88%
“…In parallel, the positive rate of influenza virus remained constantly low until early February 2023, but began to climb and reached the highest in late March before it gradually declined (8). This flu eruption was predicted due to the loosening of COVID-19 restrictions, as well as the loss of natural immunity developed for the circulating influenza virus in the past seasons prior to the year of 2023 (9).…”
Section: Introductionmentioning
confidence: 99%